Model Pencegahan Kekambuhan pada Klien Gangguan Jiwa ditinjau dari Aspek Keluarga - ganif djuwadi; Dyah Widodo (Poltekkes Kemenkes Malang, 2021)
According to WHO the number of clients with mental disorders will continue to increase until it reaches 450 million people worldwide in 2013. The number of mental disorders from the Basic Health Research in 2013 found East Java 2.2 per mile are in fourth place severe mental disorder in Indonesia. Client care mental disorders so it takes patience, the role of the family is very important because the family is the key to development and progress of the client. The general objective of the research is to find a model of prevention of recurrence in clients with mental disorders from the family aspect. This type of study design was cross-sectional, with a sample of some families who live with mental illness clients in East Java appropriate inclusion criteria, with a sample size of 205 people taken by consecutive sampling technique. Time data collection on October-November 2016 in the outpatient clinics of Mental Health Hospital Dr. Radjiman Wediodiningrat Lawang. Collecting data using a questionnaire which is based on the theory of Imogene M. King. Analisis data using SEM path analysis test with an alpha of 0.05. The result showed causal pathway model fit prevention of recurrence that: 1) Line indirect interaction effect on the prevention of relapse, as it passes communication variables; 2) Line of time there are two paths that is directly to the prevention of recurrence and indirect pathways through the role of the family; 3) Line perception indirect effect on the prevention of recurrence, because it should be the role of the family. The role of the family have the most powerful influence among the other variables in the prevention of recurrence with estimated value of 0.634. Suggested models on the prevention of recurrence prevention of mental disorders client aspect of this family can be used as the basic for the promotion of health, with emphasis on aspects of the family, especially the role of the family, interaction and communication that is based on the perception of the condition of mental disorders as well as the availability of family time for the client.